Therapeutic potential of Tualang honey formulation in osteoarthritis: a comparative study in New Zealand white rabbit models - Mohamad Amri, Nur Fathonah; Abd. Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Hassan, Habibah; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli (Malaysian Orthopaedic Association, 2024)
INTRODUCTION: Osteoarthritis (OA) is a prevalent degenerative joint disease with significant global impact. Honey has shown therapeutic potential in treating OA1. This study aims to evaluate the therapeutic potential of Tualang Honey Formulation (THF) in the management of OA using a New Zealand White Rabbit (NZWR) model, in comparison to the control group.